Леса высокой природоохранной ценности Северо-запада Пермского края - Слащев (Slaschev Dmitry), Дмитрий Николаевич; Санников (Sannikov Pavel), Павел Юрьевич (Географический вестник=Geographical bulletin, 2017)
Концентрация лесов высокой природоохранной ценности (ЛВПЦ). является одной из систем оптимизации лесного хозяйства, которая реализуется во многих странах мира на протяжении двух десятков лет. HIGH CONSERVATION VALUE FORESTS OF NORTH-WESTERN PART OF PERM REGION The conception of high conservation value forests (HCVF) is one of the optimization systems of forestry planning. Many countries use this system for twenty years. In the article the conception’s principles and criteria were applied on the territory of Komi-Perm region. As a result 8 from 11 subtypes of HCVF were identified, summary map of HCVF was created and recommendations for changing forestry mode for each type of HCVF were given.